The effect of government-designed export promotion service use on small and medium-sized enterprise goal achievement: A multidimensional view of export performance - ZAMANTILI NAYIR, DİLEK (ELSEVIER SCIENCE INC, 2012)
Extant literature is equivocal on the effect of government-designed export promotion instruments and services (EPS) on firm performance. Moreover, literature examining the effects of EPS on exporting firms' success is dominated by a single performance perspective, namely, financial goal achievement. Further, the majority of the studies are conducted in developed countries, with limited attention to exporters in developing countries. In order to address these gaps, this study examines the impact of EPS use on export goal achievement of small and medium-sized enterprises (SME) from a developing country, while adopting a four-dimensional view of export performance. Based on a survey of 143 firms in Turkey, the findings suggest that EPS use improves all four export performance dimensions considered, namely, financial, stakeholder relationship, strategic, and organizational learning goal achievements. The article also delineates the performance effects of specific EPS. For example, stakeholder relationship goal achievement is influenced by only one EPS considered, namely, informational materials (e.g., brochures, pamphlets) on exporting. The paper concludes with a discussion of the implications for scholars, public policy makers, and managers. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Export promotion instruments; Export promotion services; Export performance; Small- and medium-sized enterprises; Turkey; COMPETITIVE ADVANTAGE; FIRM; KNOWLEDGE; STRATEGY; PROGRAMS; INTERNATIONALIZATION; INTENSITY; MODEL; DETERMINANTS; ASSISTANCE